2016
DOI: 10.4018/ijegr.2016100103
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Perspective of an e-Diplomacy Maturity Framework

Abstract: Diplomacy forms the basis of interaction for countries throughout the globe, while propelling cordial international relations in a wide array of socio-cultural and political. This research outlines an innovative conceptual structure for examining the maturity and feasibility of e-diplomacy. The proposed e-diplomacy maturity framework is a derivative of literary analysis on e-government maturity model, ICT growth of stage theories, coupled with theoretical information and practical features of diplomacy. The e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Such models are important in developing sustainable e-government services since they give a strategic framework for implementing e-government initiatives (Almarabeh & AbuAli, 2010;Chohan et al, 2020). Ranging from basic to advanced online interaction skills, the e-government maturity model is divided into different phases (Almuftah et al, 2016). These phases indicate how far a country has progressed in terms of e-government maturity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such models are important in developing sustainable e-government services since they give a strategic framework for implementing e-government initiatives (Almarabeh & AbuAli, 2010;Chohan et al, 2020). Ranging from basic to advanced online interaction skills, the e-government maturity model is divided into different phases (Almuftah et al, 2016). These phases indicate how far a country has progressed in terms of e-government maturity.…”
mentioning
confidence: 99%
“…Finally, the study is concluded followed by suggestions for future research. E-government is a 21st-century technological innovation that aims to improve citizen satisfaction by utilizing ICTs such as the Internet and the Web (Almuftah et al, 2016;Al-Shboul et al, 2014). It has evolved into a critical tool for delivering government services in a more efficient, effective, and transparent manner (Joshi, 2018).…”
mentioning
confidence: 99%